As territorialidades específicas como categoria de análise na construção do direito de propriedade das Comunidades Quilombolas de Alcântara - Lopes, Danilo da Conceição Serejo. (2015)
The Federal Constitution of 1988 (FC/88) established the right of ownership of the remaining quilombo communities in Brazil. It begins a new form of property, bringing a new legal look at the content of this institute.Previously, the legal interpretation was regarded as an affirmation of absolute private property, alienable and transferableThe article 68 of the Transitory Constitutional Provisions Act (TCPA) da FC/88 established the so-called “commom property”. By coining the concept of territory, it takes intoaccount the trajectory crossed by the social group in question to seek to understand the property rights and the different ways to actuate it, or even to understand the expectation of rights for each group, for each community. This is the challenge this work proposes, having the social conflict experienced by quilombola communities of Alcântara in the state of Maranhão, taken as an analytical category, the self-appointed land of poverty, as a research field. Construct an interpretive scheme "unusual", that is, that does not follow a linear, either, a chronology of events. This work is concerned in analyzing the facts and events related to the trajectory of the quilombola communities confined to the self-appointed land of poverty, keeping care to establish an analytical connection with the ultimate goal of the research, the right of ownership. It is presented in this study, the situations referred to social conflict of Alcântara communities due to the implementation of the Space Base rockets in its territory in the 1890s; the construction of specific territorialities; and how these situations are triggered to claim and assert the right to property under Article 68 of the FC / 88 of TCPA. First of all, in vestibular chapter, it discusses the trajectory of the author who is confused with the field and the situation studied. Therefore, we seek to suspend given knowledge or first experience, to then submit them to a reflexivity process.